Toll‐interacting protein in the freshwater fish Labeo rohita exhibits conserved structural motifs of higher eukaryotes and is distinctly expressed in pathogen‐associated molecular pattern stimulations and bacterial infections. (19th July 2021) - Mohanty, Arpita; Sadangi, Sushmita; Paichha, Mahismita; Saha, Ashis; Das, Surajit; Samanta, Mrinal
Abstract: Toll‐interacting protein (Tollip) is a critical regulator of TOLL‐ like receptor (TLR)‐signaling pathway. It is predominantly associated with TLR2 and TLR4 during acute inflammatory conditions and inhibits the TLR‐mediated nuclear factor‐kappa activation by suppressing the autophosphorylation of interleukin‐1 receptor‐associated kinase and its kinase activity. This article describes the Tollip of Labeo rohita ( LrTollip ), a highly valuable freshwater fish from the Indian subcontinent. The full‐length LrTollip complementary DNA (1412 nucleotides) encodes a 276‐amino acid (aa) protein, depicting a highly conserved target of the Myb1 (Tom1)‐binding domain (TBD; 1–53 aa), conserved core domain 2 (C2; 54–151 aa), and coupling of ubiquitin to endoplasmic reticulum degradation (CUE; 231–273 aa) domains of mouse and human counterparts. The key amino acids exerting the critical functions of Tollip, such as phospholipids recognition and ubiquitination, are present in the C2 and CUE domains of LrTollip, respectively. LrTollip is widely expressed in the kidneys, gills, spleen, liver, and blood, and among these tested tissues, the highest expression is observed in blood. In response to TLR ligands and NOD‐like receptor (NLR) ligands stimulations and Aeromonas hydrophila, Edwardsiella tarda, and Bacillus subtilis infections, LrTollip gene expression is induced in various organs/tissues with remarkable difference in their kinetics. These data together suggest the important role of LrTollip in TLR‐ and NLR‐signal transduction pathways and immune‐related diseases in fish.